Kapasitas Daerah Banjarnegara Dalam Penanggulangan Bencana Alam Tanah Longsor - Amni Zarkasyi Rahman (JURNAL ILMU SOSIAL, 2017)
Capacity assessment is a parameter in determining the success of disaster risk reduction. The reference for the assessment of capacity in Indonesia is the Hyogo Framework for Action (HFA) agreed by 160 countries in disaster risk reduction efforts. The implementation of the HFA in Indonesia is ACT 24/2007 about the disaster relief. The capacity assessment was conducted to find out how disaster mitigation efforts in Banjarnegara by looking at disaster mitigation priorities. The purpose of this study was to describe the score capacity in disaster management and disaster risk reduction efforts.The results of this research is the capacity score disaster relief in the region reached 70.46% from 88 indicators so that fall into the category B. It means capacity in Banjarnegara district into disaster management can already be said either. From these results, the main concern is the basic risk factors reduce the efforts through the establishment of "Desa Tangguh Bencana".